Religion Teacher's Strategy in Instilling Disciplinary Character in Students of SDN 104257 Sekip - Nadia Salsabila Putri; Selvina Rahmi Lubis; Ramadhan Wahyudi; Mutiara Putri Nabila; Bani Amirul (Publikasi Inspirasi Indonesia, 2024)
The purpose of this research is to find out the strategy of religion teachers in instilling the character of religious discipline in students of SDN 104257 Sekip. This research uses a qualitative research design with data collection methods conducted as interviews and documentation. The results of this study indicate that there are three strategies used by religious teachers in instilling students' religious discipline character, including, (1) providing Islamic religious education, religious education has a vital role in developing the disciplined character of elementary school students. Through religious education, students not only recognize religious teachings and community beliefs but also understand the disciplinary values contained in religious teachings. (2) providing coaching, several things are done in carrying out the coaching process for undisciplined students, such as punishing students by writing the holy verse of the Qur'an on as much as 1 sheet and ordering them to memorize short surahs, if the two coaching is not well realized, then parents will be summoned. And (3) using the lecture method, in the lecture, the teacher can explain why discipline is important in students' lives, both for academic success and character development.